Mangrove Health Index in Martajasah Mangrove Ecotourism, Bangkalan Regency East Java, Indonesia - Akhmad Farid; Eko Setiawan; Apri Arisandi; Moch. Yusron (Jurnal Wilayah dan Lingkungan, 2024)
Mangrove areas need to be considered from the condition of distribution and density of mangrove forests for future mangrove forest management planning, especially on Madura Island, especially Martajasah mangrove ecotourism. The purpose of this study is to determine the type of mangrove, canopy cover, and mangrove health index. The method used in this study is observation, which is to know the general overview of the research to be carried out. The selection of the research location was determined by the stratified random sampling method. The canopy cover on the mangrove was measured using the Hemispherical Photography method using the front camera of the OPPO Reno 6 phone with a camera resolution of 8 megapixels with a 180° angle of view at the point of taking the photo. The results of this study found 7 types of mangroves, including Sonneratia alba, Sonneratia caseolaris, Rhizophora apiculata, Rhizophora mucronata, Avicennia alba, Avicennia marina, and Lumnitzera racemosa. The percentage of canopy cover obtained an average score of 63.44% or in the solid category. This indicates that the mangrove ecosystem found in Martajasah mangrove ecotourism is in a good category. The Mangrove Health Index in Martajasah Mangrove Ecotourism is included in normal (33-66%).